A HIDDEN ANOMALY: DELAYED PRESENTATION OF A GIANT CHOLEDOCHAL CYST IN ADULTHOOD - Sakshi Kumari; Lav Modh; Pooja Parashar; Purshotam Dass Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Choledochal cyst, a rare congenital anomaly involving bile duct typically present as cyst. There are 5 subtypes of choledochal cyst are classified by Todani, in which type IV is more commonly seen and type I and IV have much greater risk of malignancy then any other types which are commonly benign in nature. Not many cases of choledochal cyst are reported in literature. He we are reporting a case of thirty-five-Year-old lady presented with a large upper abdominal mass but without jaundice and on evaluation it was found out be a giant choledochal cyst of typeIVa and patient underwent dilated choledochal cyst excision with Roux-en-Y-hepaticojejunostomy and cholecystectomy at the junction of right and left hepatic duct.  Keywords: Bile duct cyst, Choledochal cyst, giant choledochal cyst.